SAFETY LOCKER USING IOT AND CLOUD COMPUTING. - KAUSHIK, ISHA; GUPTA, VARUN; PETER, J. SELVIN PAUL (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Security is becoming a very critical topic in today's world. The protection of our valuables still scares us. To safeguard sensitive information such as records, money and many more, security lockers and safe boxes are used worldwide. Only if the key to the locker is in good hands should it keep the details safe. The person does not know who did so whether someone else cheated or grabbed the key and took the details away. To avoid this the device prevents the use of a physical key by forcing the user to use an ID card to unlock the locker. The administrator is able to monitor users to give them authorization to use the locker, and the administrator can even verify whether and from whom the locker was accessed, thus avoiding data from being compromised. As described above the device uses technology to ensure the security and protection of the data contained in the locker. To store the passwords of all the users, a database management scheme is maintained. A user just wants one thing for this system and that is a computer that has the internet, and so the user will be able to execute all the operations from anywhere using that device, making the system easier to access and simple to handle.